TECHNOLOGY FOR DEVELOPING TRADITIONAL COSSACK CULTURE BY ORGANIZATIONS OF TERRITORIAL PUBLIC SELF-GOVERNMENT IN VOLGOGRAD AREA - Anatoly Solomonovich Krapivensky; Oksana Ivanovna Kolomok; Natalia Vasilievna Zenina (Вестник Северо-Кавказского федерального университета)
The article focuses on the issue of improving the performance in territorial public self-government organizations (TPS) aiming at the development of the regional culture through universal technologies related to management and PR.